The land and people of Kenya - Kaula, Edna Mason (Philadelphia : Lippincott, 1968)
Describes the geography, history, peoples, and customs of this East African country. Also discusses the recent progress made in education a nd the economy.
Keywords: Kenya -- Juvenile literature